2020
DOI: 10.1371/journal.pone.0238714
|View full text |Cite
|
Sign up to set email alerts
|

How different autonomous vehicle presentation influences its acceptance: Is a communal car better than agentic one?

Abstract: Public acceptance of autonomous vehicles (AVs) is still questionable. Nevertheless, it can be influenced by proper communication strategy. Therefore, our research focuses on (1) the type of information concerning AVs that consumers seek and (2) how to communicate this technology in order to increase its acceptance. In the first study (N = 711) topic modeling showed that the most sought for information concern the communion and the agency of AVs. In the second, experimental study (N = 303) we measured the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 141 publications
(251 reference statements)
0
4
0
Order By: Relevance
“…A study that framed self-driving vehicles as producing environmental benefits reported greater trust among participants, leading to their higher risk acceptance of and willingness to ride in the vehicles (Liu et al, 2019c). Hryniewicz and Grzegorczyk (2020) also found that describing AVs with different contents (communal vs agentic) influences AV acceptance.…”
Section: Framing Effectmentioning
confidence: 97%
“…A study that framed self-driving vehicles as producing environmental benefits reported greater trust among participants, leading to their higher risk acceptance of and willingness to ride in the vehicles (Liu et al, 2019c). Hryniewicz and Grzegorczyk (2020) also found that describing AVs with different contents (communal vs agentic) influences AV acceptance.…”
Section: Framing Effectmentioning
confidence: 97%
“…As such, this study focuses on examining persuasion effects of gendered content in health communication in the UK. Our motivation to focus on this question is driven by a substantial volume of research on the effectiveness of gendered content in contexts outside of health communication and outside the UK [ 13 , 22 26 ]. Hence little is known about the effectiveness of gendered content in health communication in the UK specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Further, most of the prospective sources on the matter agree on the fact that (just like in any other market) users' perceptions and attitudes play a crucial role for the future of automated vehicles (AVs) and their related transportation dynamics, even though the available empirical information in this regard remains considerably limited [4,5].…”
mentioning
confidence: 99%
“…However, and as a consequence of different technological, safety and mass communicationrelated constraints, some studies have argued that the intention to shift to fully automated vehicles could decrease if potential users do not attribute enough value to their different features, especially those related to safety, efficiency and stability [6]. An example of it is the considerable number of non-specialized sources often under or overstressing the actual capabilities of automated vehicles that, far from improving their market-transforming possibilities, can negatively influence both potential consumers' perceptions, same as the willingness of policymakers and transport planners to further invest on adapting road infrastructures as a way to enhance a safer, more sustainable and cost-effective mobility [1,4].…”
mentioning
confidence: 99%